Penggunaan Media Digital untuk Promosi dan Peningkatan Social Awareness Komunitas UMKM Makanan Warung Gereja Kristen Indonesia (GKI) Cikarang (WGC) - Marsefio Sevyone Luhukay; Revi Narwastu Paparang; Adissa Destriana Nurmala; Dinara Hizkiarin Verga; Gracia Gloria Irene (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The COVID-19 pandemic caused many businesses to collapse, especially for micro, small and medium enterprises (MSME). Therefore, business operators must be able to adapt quickly to circumstances and move to the digital realm to try to rise and attract many consumers. Komunitas Warung Gereja Kristen Indonesia (GKI) Cikarang (WGC) is a community established by GKI Cikarang to help congregations who have businesses to keep up their business during the pandemic. However, the problem is that the WGC community is only limited to promoting the business of congregations in the church market, not yet widely known. Moreover, most of the congregations that is a part of WGC are still unable to use social media to help their businesses. Therefore, through this Capstone program, part of pengabdian pada masyarakat or service learning, we want to educate about the use of digital media for promotion and social awareness improvement in the WGC community, especially in the food sector. Keywords: MSME, Digital, Social Media, Promotion, Social Awareness